2019
DOI: 10.1007/s10198-019-01059-w
|View full text |Cite
|
Sign up to set email alerts
|

Subjective expectations regarding ageing: a cross-sectional online population survey in Hungary

Abstract: Background We aimed to investigate individuals' subjective expectations regarding health and happiness alongside their provisions on life circumstances for older ages. Methods A cross-sectional online survey was performed involving a representative sample (N = 1000; mean age 50.9, SD = 15.4; female 54.5%) in Hungary. Subjective expectations on health status (EQ-5D-3L/-5L, GALI, WHO-5), happiness (0-10 VAS), employment status, care time, and forms of care for ages 60, 70, 80, and 90 were surveyed. Results Curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
7
1
3
Order By: Relevance
“…Comparisons with some previous studies deserve mentioning. sHE for future ages were explored in two online surveys among the general population in Hungary [19,29]. Both confirmed that people in general expect health deterioration with age and the expected health status is worse than the actual health status of the general public from age 70 and above.…”
Section: Discussionmentioning
confidence: 97%
“…Comparisons with some previous studies deserve mentioning. sHE for future ages were explored in two online surveys among the general population in Hungary [19,29]. Both confirmed that people in general expect health deterioration with age and the expected health status is worse than the actual health status of the general public from age 70 and above.…”
Section: Discussionmentioning
confidence: 97%
“…En relación con sus propiedades psicométricas, diversos estudios reportan la existencia de un solo factor del who-5 wbi que explica entre el 56.7 % y el 70.8 % de la varianza total y una adecuada consistencia interna, con coeficientes alfa de Cronbach entre 0.66 y 0.95 (19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionunclassified
“…For instance, in the CEE countries included in this study, 'fulfilment' was valued relatively highly, whereas 'financial problems' received a relatively low weight. These differences may partly reflect differences between CEE countries and the six reference countries in terms of economic situation and labour participation as well as attitudes towards informal care [26]. According to the previously mentioned Eurobarometer survey, a substantially lower share of the population in Western European countries considered the best option for an older person who no longer manages to live alone was to live with one of their children.…”
Section: Discussionmentioning
confidence: 99%